KARAKTERISASI BATUAN INDUK HIDROKARBON DAN RESERVOAR NONKONVENSIONAL DI CEKUNGAN JAWA TIMUR BAGIAN UTARA: CHARACTERIZATION OF HYDROCARBON SOURCE ROCKS AND UNCONVENTIONAL RESERVOIR IN THE NORTHERN EAST JAVA BASIN - Airlangga, Feby; Handoyo, Handoyo; Irawati, Selvi Misnia; Wibowo, Andy Setyo (Buletin Sumber Daya Geologi, 2024)
The northern East Java Basin is one of the hydrocarbon producing basins in Indonesia with a thick source rock layer and is interesting to study as a potential unconventional reservoir in the future. In this research, integration of well data analysis and seismic inversion is used to identify the characteristics of the source rock in the studied area. Well data analysis can provide lithological information from the source rocks bearing formations, namely shale of the Prupuh Formation, dominant shale of the Kranji Formation, and limestone of the Ngimbang Formation. In addition, log data can provide information on predicting Brittleness Index (BI) and Total Organic Carbon (TOC) values ​​in the target zone. The linear regression is used to propagate BI, porosity, and TOC on the seismic data. To assist the process of distributing TOC and BI values ​​on seismic parameters, Acoustic Impedance (AI) inversion was carried out by using a model based hard constraint method to predict the AI ​​distribution. The results of this study show that the target zone is a potential zone with a medium to potential category with a TOC distribution of 1.5%-2.2%, BI of 0.2-0.46, and porosity of 0.03-0.15. Moreover, seismic inversion data also helps the distribution of petrophysical parameters in good lateral conditions following the distribution of shale source rock horizons.